REVIEW OF SHRIMP CULTIVATION TECHNIQUES IN PLASTIC (BUSMETIC) PONDS - Fatalattof. A, Ammar; Yustiati, Ayi; Andriani, Yuli (Program Studi Budidaya Perairan Universitas Mataram, 2022)
Shrimp cultivation has always been a star in the world of Indonesian aquaculture and today it is still one of the national priority aquaculture commodities. The market needs of domestic and foreign shrimp cultivation can be met by the high economic value of shrimp. There are many models of cultivation designs and shrimp farming systems that have been developed and used by farmers ranging from traditional to modern. The development of cultivation technology by utilizing marginal land by using plastic as a container for cultivation maintenance is called